Method development and validation for the simultaneous estimation of tolperisone hydrochloride and diclofenac sodium by RP-HPLC - Madasu Sravan Kumar; P.Sunitha (International Journal of Pharmacy and Analytical Research, 2015)
A validated RP-HPLC method has been developed for the determination of Tolperisone hydrochloride and Diclofenac Sodium in tablet dosage form. This method is developed by using C18 column (Inertsil ODS, 250 mm length, 4.6 mm internal diameter and 5 µm particle size) and a mixture Phosphate Buffer pH 3.0, Acetonitrile and Methanol (60:20:20) as a mobile phase. The drug was quantified by a UV detector at 242 nm. The method is linear for Tolperisone hydrochloride and Diclofenac Sodium in range of 90 to 210 µg/ ml and 30 to 70µg/ml, respectively. The percentage mean recovery of the method for Tolperisone hydrochloride and Diclofenac Sodium was found to be 99.75% and 99.38%, respectively. The proposed method was found to be linear, precise and accurate for the quantitative estimation of Tolperisone hydrochloride and Diclofenac Sodium in tablets and can be used for commercial purposes.